Air traffic control automation: for humans or people? - Brooker, Peter (Ashgate Publishing, 2005)
Are air traffic controllers humans or people? At first sight, this seems a very odd question, given that ‘humans’ and ‘people’ are near-synonyms in the dictionary and everyday usage. However, in research on air traffic control (ATC) automation the phrase ‘human-centred’ is used to mean particular aspects of people: for example, it does not usually address their motivations for embracing change or cover organisational behaviour issues. The objective here is to try to understand how the fact that air traffic controllers are people – particular kinds of people – is likely to affect the introduction of automation. This examination takes as an example a suite of computer assistance tools for en route ATC. How would these tools need to change if the fact that controllers are ‘people’ is taken into account?